PENGELOLAAN BARANG MILIK DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA PALANGKA RAYA: Management of Regional Property in the Financial Management Agency and Regional Assets in the City of Palangka Raya - Yanto, Errin Seth; Lasmaria, Tri (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2022)
This research are (1) to find out the management of regional property carried out by the Regional Financial and Asset Management Agency of Palangka Raya City. (2) To find out the factors that hinder Management Regional Financial and Asset Management of Regional Property of the Palangka Raya City Government.This research approach uses qualitative, this study usesinterview guidelines as a research instrument. Qualitatively, the study found that, based on the operational standards in the Regulation of the Minister of Home Affairs Number 19 of 2016 regarding the use, utilization, and transfer of Regional Property based on functional principles, legal certainty principles, transparency principles, efficiency principles, accountability principles, and legal certainty principles. And the results of this study show that the Management of Regional Property in accordance with the Regulation Minister of Home Affairs Number 19 of 2016 which is seen from the functional principle, the principle of legal certainty, the principle of transparency, the principle of efficiency, the principle of accountability, and the principle of value certainty at the Regional Financial and Asset Management Agency of the City of Palangka Raya has been effective and However, there are still obstacles carried out by the Regional Financial and Asset Management Agency of Palangka Raya City, namely regarding technical guidelines related to the management of regional property, the reporting basis for the person in charge of the management of regional property, and problems regarding the inventory of regional property.